ANALYSIS OF THE DIFFICULTIES OF GRADE VII H STUDENTS OF SMP NEGERI 6 PALU IN SOLVING SET STORY PROBLEMS IN TERMS OF LEARNING STYLE - Anisa, Nurul; Anggraini, Anggraini; Sugita, Gandung; Murdiana, I Nyoman (FKIP Universitas Muhammadiyah Tangerang, 2024)
This study analyzes students' difficulties in solving set story problems, taking into account students' learning styles. The research approach used a qualitative approach. Data were obtained through questionnaires, written tests and interviews. The results showed that students with visual, auditorial, and kinesthetic learning styles experienced difficulties in solving set story problems. Students with visual learning styles experience two indicators of difficulty, namely difficulty learning concepts and difficulty applying principles. For difficulties in learning concepts, students cannot use formulas that are in accordance with the conditions of the problem, namely the formula for the combination and difference of three sets. As for the difficulty of applying principles, students make mistakes in calculation activities and do not solve the problem. Students with auditorial learning styles experience all indicators of difficulty, namely difficulty learning concepts, difficulty applying principles and difficulty solving verbal problems. In the difficulty of applying concepts, students cannot translate the form of the problem, do not know what is known from the problem, students also do not use formulas that are in accordance with the conditions of the problem. In difficulty applying principles, students make mistakes in calculation activities when solving problems. In the difficulty of solving verbal problems, students make mistakes in translating problems into mathematical form, students also cannot determine the data used, and do not check the answers obtained. Students with kinesthetic learning styles fulfill all indicators of difficulty, namely difficulty learning concepts, difficulty applying principles and difficulty solving verbal problems. In difficulties in learning concepts, students hesitate in using memorization or set notation. students cannot use formulas that are in accordance with the conditions of the problem. In difficulties in applying principles, students make mistakes in calculation activities. This happens because students do not know the formula and make mistakes in using the data used. In the difficulty of solving verbal problems, students make mistakes in determining the data used, students do not check their answers again.